Dampak Penurunan Energi Terhadap Kelelahan Perawat Pada Masa Bencana Pandemic Covid-19 - Heru Suwardianto; Lilik Setiawan (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2021)
Abstract The COVID-19 pandemic causes increased burdens and anxiety when performing tasks for long periods of time and can lead to decreased energy and ultimately psychosocial fatigue. The aim of the study was to analyze the Decrease in Energy and Nurse Fatigue during the COVID-19 Pandemic Disaster. Research design using cross sectional. The study population was all nurses in Kediri City, the research sample was several nurses who were taken by accidental sampling technique. The independent variable of this research was the decrease in energy, the dependent variable of this research was the fatigue of nurses. The statistical test used the Spearmen rho test with α <0.05. The results showed that most respondents had a decrease in energy from mild to extreme (57%) and the majority of respondents experienced fatigue from mild to total fatigue (72.1%). The results showed that there were 2.3% of nurses who experienced extreme energy reduction with exhaustion or total fatigue. The results of statistical tests with Spearman's rho obtained Ρ value <0.001, which means that there is a significant relationship between decreased energy and fatigue. Lack of energy is related to the fatigue that occurred in nurses during the COVID-19 Pandemic, so prevention is needed so that nurses can carry out energy management so that it does not cause an impact from nurse fatigue. Keywords: Decrease in energy, fatigue of nurses, COVID-19 Pandemic Disaster